STUDI ANALISIS PEMIKIRAN K.H. AHMAD DAHLAN TENTANG PENDIDIKAN ISLAM DI INDONESIA - Khadafi, Muammar; Supriyanto, Agus (Turats, 2011)
Kyai Haji Ahmad Dahlan (1 August 1868 Yogyakarta - 23 February 1923 Yogyakarta), born Muhammad Darwis, was an Indonesian Islamic revivalist who established Muhammadiyah in 1912. He created Muhammadiyah in 1912 as an educational organisation as a means of realising his reformist ideals. It was quickly joined by traders and craftsmen. In 1917 added a women's section named Aisyiyah, which played a significant role in modernising the life of Indonesian women. Spreading to the Outer Islands, Muhammadiyah established a strong base in Sulawesi only a decade later after it was founded. It was one of a number of indigenous Indonesian organisations founded in the first three decades of the twentieth century;a time known as the Indonesian National Revival; that were key in establishing a sense of Indonesian nationalism, and ultimately independence. Dahlan was completely absorbed in the field of education. Aiming point on the world of education in turn drove him into the heart of the people who actually matter. Based on the description of this concept can be used later to build a more effective nation that is through education. KH Ahmad Dahlan is a man of action types that are already in place when leaving quite a lot of charitable efforts are not made. Therefore, to explore how the philosophical orientation of education Ahmad Dahlan more properly refers to how he built the educational system